State of the art: Three Dimensional (3D) Slope-Stability Analysis. Issue 5 (19th October 2016) - Chakraborty, Arunav; Goswami, Diganta
Abstract : Stability of slope is a major problem in the area of geotechnical engineering. The analysis and design of failing slopes and highway embankments requires an in-depth understanding of the failure mechanism in order to choose the right slope-stability analysis method. Two-dimensional (2D) slope-stability methods are the most commonly used methods among the engineers due to their simplicity. However, the assumptions used in these 2D methods are very simple which reduces the 3D problem to a 2D problem and hence the accuracy of the analysis results vary between the different analysis methods. The importance of 3D analysis of slope stability is greatly increased where the geometry is complex which makes it difficult to select a typical section for 2D analysis. Since 1990s, a lot many number of three-dimensional slope stability-analysis methods were developed based on limit equilibrium and finite element concept. Many of them are valid only under certain conditions. This paper basically focuses on the literature review of 3D slope stability by various researchers.